Beyond dyssynchrony in cardiac resynchronisation therapy. Issue 8 (14th July 2008) - Chung, R; Sutton, R; Henein, M Y
Abstract : Cardiac resynchronisation therapy (CRT) in the form of biventricular pacing has emerged as a therapeutic option for patients with refractory heart failure. Patient selection and optimisation for CRT is based on the measurement of electromechanical ventricular dyssynchrony by electrocardiogram and echocardiographic techniques. The final common pathway for raising cardiac output on exertion is to minimise isovolumic time and maximise useful diastolic filling time, but correction of dyssynchrony alone may not lead to global improvement in about one-third of patients. Insights into pressure relations and abnormal timing, as well as clinical management, may hold the key to optimum outcome.